Learning from career preparedness: examining the influence of person–environment fit on decent work expectations - Kou, Qi; Mohd Rasdi, Roziah (Emerald Publishing, 2025)
Purpose This study aims to examine the influence of person–environment fit on decent work expectations and the mediating role of career preparedness in the relationship between person–environment fit and decent work expectations.